A lightweight shape-memory alloy with superior temperature-fluctuation resistance - Yuxin Song; Sheng Xu; Shunsuke Sato; Inho Lee; Xiao Xu; Toshihiro Omori; Makoto Nagasako; Takuro Kawasaki; Ryoji Kiyanagi; Stefanus Harjo; Wu Gong; Tomáš Grabec; et al. (Nature, 2025)
Abstract In advanced applications such as aerospace and space exploration, materials must balance lightness, functionality and extreme thermal fluctuation resistance1,2. Shape-memory alloys show promise with strength, toughness and substantial strain recovery due to superelasticity, but maintaining low mass and effective operation at cryogenic temperatures is challenging3–6. We hereby introduce a new shape-memory alloy that adheres to these stringent criteria. Predominantly composed of Ti and Al with a chemical composition of Ti75.25Al20Cr4.75, this alloy is characterized by a low density (4.36 × 103 kg m− 3) and a high specific strength (185 × 103 Pa m3 per kg) at room temperature, while showing excellent superelasticity. The superelasticity, owing to a reversible stress-induced phase transformation from an ordered body-centred cubic parent phase to an ordered orthorhombic martensite, allows for a recoverable strain exceeding 7%. This functionality persists across a broad range of temperatures, from deep cryogenic 4.2 K to above room temperature, arising from an unconventional temperature dependence of transformation stresses. Below a certain threshold during cooling, the critical transformation stress inversely correlates with temperature. We interpret this behaviour from the perspective of a temperature-dependent anomalous lattice instability of the parent phase. This alloy holds potential in everyday appliances requiring flexible strain accommodation, as well as components designed for extreme environmental conditions such as deep space and liquefied gases.